Policy in action : the challenge of service delivery - Wanna, John (UNSW Press, 2010)
Modern governments have undergone significant change over the past 30 years. Such change has impacted on the way governments structure their organisations, deliver services and relate to their citizenry. But how has public policy formulation changed and affected the design and delivery of government programs and services in Australia? Policy in Action is the first book to address this question, offering descriptive accounts of how public services programs are designed and implemented and how they might be better managed.